The Local Wisdom Model in Change of Farmer Behavior and Its Impact on Adoption of Technology Special Efforts (UPSUS) Maize Plants in North Central Timor District - et al., Marsianus Falo (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to describe the characteristics of farmers and analyze the role of local wisdom in changing farmers' behavior and analyze the level of adoption of Upsus maize technology in North Central Timor District. The unit of analysis in this research is Upsus farmer participants, the determination of respondents is done by technique: first, the determination of key informants to obtain in-depth data information from farmers is determined by Snowball Sampling. Secondly, the determination of informants which is carried out intentionally (purposive) addressed to figures who have direct or indirect involvement in the Upsus corn program. Primary data collection was carried out through a questionnaire that was prepared in August-December 2019. In-depth interviews (FGD) were conducted in Insana Sub-district, TTU-NTT District in Upsus participating farmer groups. Secondary data collection was carried out by collecting data from the Department of Agriculture, BPS and related agencies. The analysis showed that the characteristics of farmers (age is in the adult category, formal education, non-formal education in the low category, experience of farmers in the high category, while the area of ​​land, and cosmopolitan is in the very low category), while the local wisdom model for changes in farmer behavior has not run optimally. The local wisdom model in TTU District by farmers is generally aware of the assistance provided by the government namely Upsus corn plants, but it does not take into account the farming cycle that is owned and known to farmers and greatly influences changes in farmer's behavior in corn farming. It can be seen that the harmonious relations in carrying out the corn plant rituals which have not proceeded as expected, namely the entire stages of maize farmings are not carried out such as the rituals of Ta'poen Fi'ni (Removing Seeds), Pen Su'fa (Corn Flowering Time), Ta Fe ' u (New Food), T'sek Pena (Harvesting Corn), Ta'kbu Pena (Tying Corn), Tsef pen sma'naf (Opening the Spirit of Corn), T'hab nin (Preparing for Storage), Ta sae be noe Lopo (Putting into Lopo). The changes in farmer's behavior towards the innovation of Upsus maize in TTU are in the low category. If it is seen from the farmers' acceptance in Upsus maize, the farmers experienced an increase in the innovator category, but there was also an increase in the late adopter category which showed that farmers were always careful about innovations in corn Upsus, waiting for many people to have tried and chosen / adopted an Upsus innovation applied to maize.